2020
DOI: 10.3847/1538-4357/abc6b0
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interstellar Grain Growth through Polarimetry in the Taurus Cloud Complex

Abstract: The optical and near-infrared (OIR) polarization of starlight is typically understood to arise from the dichroic extinction of that light by dust grains whose axes are aligned with respect to a local magnetic field. The size distribution of the aligned grain population can be constrained by measurements of the wavelength dependence of the polarization. The leading physical model for producing the alignment is that of radiative alignment torques (RAT), which predicts that the most efficiently aligned grains are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…Lefèvre et al 2014;Ysard et al 2016;Juvela et al 2020), and (iii) the polarisation (e.g. Fanciullo et al 2017;Vaillancourt et al 2020). Depending on the dust model details and the gas local properties, the accretion of the (sub-)nanometre-sized grains on larger grains is not expected to take more than a hundred to a few thousand years in the outskirts of molecular clouds (e.g.…”
Section: Column Density Mapmentioning
confidence: 99%
“…Lefèvre et al 2014;Ysard et al 2016;Juvela et al 2020), and (iii) the polarisation (e.g. Fanciullo et al 2017;Vaillancourt et al 2020). Depending on the dust model details and the gas local properties, the accretion of the (sub-)nanometre-sized grains on larger grains is not expected to take more than a hundred to a few thousand years in the outskirts of molecular clouds (e.g.…”
Section: Column Density Mapmentioning
confidence: 99%
“…Further a marginal correlation between λmax and AV was found (e.g. in studies Whittet et al 2001;Andersson & Potter 2007;Whittet et al 2008;Il'in et al 2018;Vaillancourt et al 2020). We have shown the dependence of λmax on AV in Figure 9a for observed region NGC 2345.…”
Section: Wavelength Of Maximum Polarization As Function Of Extinction...mentioning
confidence: 53%
“…Whittet et al 2008;Il'in et al 2018). However, in some studies Andersson & Potter (2007); Vaillancourt et al (2020), a relatively smaller slopes (≈ 0.03) were found. According to radiative alignment theory, grains are aligned when anisotropic radiation is sufficiently strong to spin-up grains to superthermal rotation (Hoang et al 2021).…”
Section: Implications For Grain Alignment Mechanismsmentioning
confidence: 88%
“…As an alternative (or complementary) to "super-paramagnetic grains" Purcell (1979) proposed that if the grains could be spun up to rotation speed significantly above the thermal energy of the gas, thermal gas-grain collisions would not be as efficient in randomizing the grain orientation. He suggested that the most likely source of such "suprathermal spins" would be photoelectric emission from the grains and, especially, the ejection of newly formed hydrogen molecules (van de Hulst 1948) from the grain surface.…”
Section: Introductionmentioning
confidence: 99%